Skrining pada Masyarakat Komorbid sebagai Upaya Pencegahan dan Pengendalian Penyakit Tidak Menular melalui Kegiatan Posbindu - Adi Sucipto; Desty Ervira Puspaningtyas; Yunita Indah Prasetyaningrum; Ametkabal K. Luturmas; I Komang Suadana Adi Pranata; Hafizha Rahma Zhafira; Nuri Kamalia Zulfa; Qotrunnada Firdausi (Jurnal Pengabdian Masyarakat: Tipis Wiring, 2023)
Comorbid (disease) comorbidities experienced by patients at the start of treatment can increase the risk of death. The most common co-morbidities reported to date are old age, hypertension, cardiovascular disease, diabetes, stroke, obesity, smoking, lung disease, and chronic kidney disease. Purwomartani Village is one of the Yogyakarta areas that have health problems with various comorbidities. The incidence of comorbidities in Indonesia is quite high, one of which is in Padukuhan Kadisoka, Purwomartani Village. The majority of people with comorbidities do not realize that they have years of risks and dangers if they are not controlled properly, and this can even increase the risk of death. This has an impact on high medical costs due to the length of treatment. This community service aims to detect non-communicable diseases through screening activities in people with comorbidities. The types of activities carried out at this service are in the form of screening for nutritional status which includes measuring weight, height, abdominal circumference, body mass index (BMI), blood pressure screening, and simple laboratory examinations which include checking blood sugar levels while, cholesterol, and acid tendon. This screening activity was carried out on 31 respondents from the Kadisoka Purwomartani Sleman Hamlet community. The results of the examination showed that most of the respondents had abdominal circumference in the obese category of 27 respondents (87.1%), BMI for the majority of the obese degree 1 category were 14 respondents (45.2), most of the blood pressure including hypertension were 14 respondents (45, 2%), blood sugar levels were mostly normal for 24 respondents (77.4%), uric acid levels were mostly hyperuricemia for 16 respondents (51.6%) and cholesterol levels, for the most part, were hypercholesterolemia namely 21 respondents (67.7%) . The results of this screening are expected to increase public awareness about the dangers of death, especially in people with comorbidities. This service will then be followed up by the service team and the Kalasan Health Center to be able to maximize the use of Posbindu as a means of screening for non-communicable diseases for the prevention and control of PTM through Posbindu activities.